Simultaneous transcatheter closure of intralobar pulmonary sequestration and patent ductus arteriosus in a patient with infantile Scimitar syndrome - Eyup Aslan; Ibrahim Cansaran Tanidir; Murat Saygi; Sertac Hanedan Onan; Alper Guzeltas (KARE Publishing, 2015)
Scimitar syndrome is a rare disease associated with a right lung sequestration vascularised by arteries arising from the abdominal aorta and abnormal venous drainage into the inferior vena cava. The infantile form is generally presented with severe heart failure, pulmonary hypertension and respiratory distress. It may be associated with various intracardiac defects, including atrial septal defects, ventricular septal defects, patent ductus arteriosus or more complicated structural congenital heart defects. Here, we present a 2-month-old girl with Scimitar syndrome whose pulmonary arterial pressure decreased after transcatheter patent ductus arteriosus closure and embolization of the anomalous systemic arterial supply.